Constraining Mineral Potential of the Alexander Terrane Near Porcher Island, Northwestern British Columbia - Kadulski, Brennan M.; Potter, Julia J. (My University, 2010)
The Paleozoic Alexander terrane in northern British Columbia and Alaska contains two island arc sequences, including, the late Proterozoic to Cambrian Wales Group and the early Ordovician to late Silurian Descon Formation. Both of these sequences are thought to represent volcanic arc assemblages composed of sedimentary, volcanic, and plutonic rocks and their metamorphic equivalents. Both the Wales and Descon have significant volcanic massive sulfide potential based on alteration patterns, prospects, showings, and favorable rock types. Mapping and sampling of the Wales Group and Descon Formation on Porcher Island, along with geochemical and geochronological data is critical for understanding and constraining the VMS economic mineral potential of the Alexander terrane.
Color poster with text, images, and maps.
Keywords: Minerals--Alaska; Minerals--British Columbia; Volcanic ash, tuff, etc.--Alaska; Volcanic ash, tuff, etc.--British Columbia; Geology--Alaska; Geology--British Columbia; Posters